Daily temporal homeostasis in the coral Acropora digitifera - Rosenberg, Yaeli; Doniger, Tirza; Lampert, Sarit; Sinniger, Frederic; Harii, Saki; Levy, Oren (Frontiers in Marine Science, 2023)
The study aimed to gain a deeper understanding of the daily fluctuations in gene expression at a transcript level in the coral Acropora digitifera and create a comprehensive map of the biological processes that occur under natural environmental conditions. The coral is a key organism in marine ecosystems, and understanding its physiology and the adaptation mechanisms it uses to cope with daily environmental changes is vital for its survival and the preservation of coral reefs. The study’s results showed that certain genes in the coral exhibit specific patterns of expression at different times of the day. These genes play critical roles in regulating a wide range of physiological and behavioral processes, such as metabolism, development, and DNA damage repair. During the day, the coral expends energy on growth and development, and these genes are actively involved in these processes. On the other hand, at night, the coral’s focus shifts toward repair and recovery. The genes that are active during this period are involved in processes like DNA repair, hypoxia response, and transcription. This is a crucial time for the coral, as it’s exposed to a range of environmental stressors that can damage its DNA and impact its overall health. In conclusion, this study provides valuable insights into the cyclic regulatory processes that help the coral adapt to daily external variations and sustain its physiology. It highlights the importance of understanding the daily rhythms of gene expression in marine organisms and the role they play in maintaining the health of coral reefs. This research can be used to develop strategies to preserve coral reefs and mitigate the effects of environmental changes on coral physiology.